Descripción de una nueva especie del género Rochaina (Blattodea: Nyctiboridae) para México - Estrada-Álvarez, Julio C. (Instituto de Ecología, A.C., 2022)
A new species of the Neotropical genus Rochaina Estrada-Álvarez, Lopes, Maes, Sánchez-Ocampo & Sormani, 2021 is described for the Mexican Pacific coast, being the eighth of the genus and second for Mexico.